Characteristics of Grape Growing in Altinsay District and Detection of Fungal Diseases in it - Sattarov Abdumurod Sattarovich (International Journal on Integrated Education, 2022)
The article describes the specific characteristics of viticulture in Oltinsoy district of Surkhan oasis and the issue of determining fungal diseases in it. Also, the methods of preventive and agrotechnical measures in the fight against diseases of grapes, the advantages of using more potassium to increase the plant's resistance to diseases, and the results of experimental work on the fight against fungal diseases in the vineyards of the district are written.